2011
DOI: 10.1159/000322583
|View full text |Cite
|
Sign up to set email alerts
|

Thymulin Gene Therapy Prevents the Histomorphometric Changes Induced by Thymulin Deficiency in the Thyrotrope Population of Mice

Abstract: There is evidence of the existence of a bidirectional relationship between the thymus gland and the thyroid axis. Since the thymic peptide thymulin possesses hypophysiotropic activity, we undertook the task of assessing the histomorphometric changes induced by thymulin deficiency on the thyrotrope population of normal mice and the action of neonatal thymulin gene therapy on the thyrotropin (TSH)-cells of nude mice. C57BL/6 mice were subjected to immunoneutralization of circulating thymulin from postnatal day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Immunoneutralization experiments lend support the idea that thymulin may be a physiologic mediator of the perinatal influence of the thymus gland on the maturation of the neuroendocrine axis. Thus, immunoneutralization of serum thymulin from age 1 to 33 days in normal C57BL/6 mice induced clear morphologic changes in most adenohypophysal endocrine cell populations [50][51][52] as well as a reduction in serum levels of gonadotropins, TSH, PRL and GH ( Fig. 1).…”
Section: Hypophysiotropic Activity Of the Hormone Thymulinmentioning
confidence: 90%
See 1 more Smart Citation
“…Immunoneutralization experiments lend support the idea that thymulin may be a physiologic mediator of the perinatal influence of the thymus gland on the maturation of the neuroendocrine axis. Thus, immunoneutralization of serum thymulin from age 1 to 33 days in normal C57BL/6 mice induced clear morphologic changes in most adenohypophysal endocrine cell populations [50][51][52] as well as a reduction in serum levels of gonadotropins, TSH, PRL and GH ( Fig. 1).…”
Section: Hypophysiotropic Activity Of the Hormone Thymulinmentioning
confidence: 90%
“…NTGT has also been reported to partially prevent the alterations that occur in some of the endocrine cell populations of nude mice after puberty. Thus, NTGT prevented the reduction in the number of gonadotrophs, thyrotrophs, corticotrophs and somatotrophs in adult nudes [51,[80][81][82]. NTGT also prevented, to a varying extent, changes in other histomorphometric parameters in the anterior pituitary of adult nudes.…”
Section: Neonatal Gene Therapy For Thymulin In Nude Micementioning
confidence: 99%
“…Thus, neonatal immunoneutralization of circulating thymulin in otherwise normal C57BL/6 mice induced significant morphologic alterations in most anterior pituitary endocrine cell populations [50,51] as well as a reduction in circulating levels of gonadotropins, thyrotropin, PRL and GH [ 51, 52 ; unpubl. obs. ].…”
Section: Hypophysiotropic Activity Of Thymulinmentioning
confidence: 99%
“…Thus, NTGT prevented the reduction in the number of gonadotrophs, thyrotrophs and corticotrophs in adult nudes [51,60,61] . NTGT also prevented, to a varying extent, changes in other histomorphometric parameters in the anterior pituitary of adult nudes.…”
Section: Neonatal Gene Therapy For Thymulin In Nude Micementioning
confidence: 99%
“…Thus, it was observed that thymulin stimulates PRL release in dispersed rat pituitary cells [9], whereas others have reported that thymulin inhibits PRL release in incubated rat pituitary fragments [8]. Furthermore, we have found in in vivo studies that thymulin is an important player in the communication of the thymus with the gonadotropic, corticotropic and thyrotropic axes [13,14,15,16]. …”
Section: Introductionmentioning
confidence: 99%